Pemerolehan Morfosintaksis pada Anak Usia 3 Tahun - Adiprana Yogatama (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2013)
There is a close relationship between the structure of words and the structure of sentences. In some languages it is even difficult to tell whether a particular word formation is a word or a sentence. Language acquisition theory has advanced in many ways since Brown (1973), but we are still dealing with many of the same basic methodological issues be confronted, Elaborating on Brown's approach, researchers have formulated increasingly reliable methods for measuring the growth of grammar, or morphosyntax, in the child. In this paper, the writer tries to study the morphosyntax acquisition in Indoneian childrn age 3 years. This is a basic research before continuing the next study in children's second language acquisition.